SISTEMÁTICA PARA AVALIAÇÃO DA CONFORMIDADE: UMA PROPOSTA PARA USO DE CÃO-GUIA - Brito, Joana D‟arc de (2009)
The objective of the present study is to identify and to consider which are the main requirements for the Evaluation of Center of Training, Trainers and the Independent Instructors of guide-dogs, in order to follow what the Law n.º 11,126, of 27 of June of 2005 prescribes, concerning the necessities of adaptation of the involved segments. This research was structured in 3 (three) stages. At a first moment it was used bibliographical sources for the survey of works of reference for the development of the literature revision. At a second moment, was of basic importance the accomplishmed of a documentary research, having as target the document search that could contribute for the basement of the relative study to the subject in question. At a third moment, a research of field has become fullfilled with intentions to create a space of construction of diverse looks on the real. The data have been treated from the Analysis of the Speech. It can be concluded that the present proposal of regulation for evaluation of the schools of guide-dogs, instructors and trainers, prioritized peripheral and irrelevant aspects for the final result of formation of the pairs (users/guide-dog).